STUDI ANALISIS ASPEK-ASPEK KEBERHASILAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 01 KARANGMALANG GEBOG KUDUS - Ahmad Falah (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
The Reseacrh in reality , mearning  of the teacher, methods, curriculum, studens, environment and insfrastructure and evaluation of teaching  and learing  have not improved the Islamic education achievement.  But  all  aspect  or dimentions from  metdos until evaluation is  to enhance the success and quality standart of Islamic education especially in  basic institusioanl / school (SD) of Karangmalang Gebog Kudus.